Models, Languages, and Tools for Concurrent and Distributed Programming : Essays Dedicated to Rocco De Nicola on the Occasion of His 65th Birthday /: Essays Dedicated to Rocco De Nicola on the Occasion of His 65th Birthday. (2019) - Unknown
No abstract available